Femoral neck morphology differentiates femoral neck from vertebral osteoporotic fracture - N. Malavolta; M. Frigato; R. Mulè; C. Ripamonti (PAGEPress Publications, 2003)
Mineral density and bone geometry are the two main biomechanical factors related to bone resistance to stress. Objective: In this study we assess whether differences in the proximal femur geometry (PFG) characterize different types of osteoporotic fractures. Methods: We studied 533 postmenopausal women aged 50 - 85. They were divided into four groups matched for bone mineral density at the femoral neck; without fractures (165), vertebral fractures (139), trochanteric fractures (102), and hip fractures (127). Dual X-Ray absorptiometry (DXA) scans at the spine and at the hip were carried out to measure bone mineral density and the DXA images were used to define the proximal femur geometry parameters of the hip. Results: Age, height, vertebral BMD and PFG parameters (i.e.femoral neck-shaft angle (NSA) and hip axis length (HAL) were different when all four groups were compared by the Anova test. Patients with vertebral fractures were then compared by multivariate analysis to those with trochanteric fractures. The variables that discriminated the two groups were: age, age at menopause, weight, height, and vertebral BMD, but not PFG. Comparing vertebral to hip fractures the distinguishing variables were: vertebral BMD, height, NSA and HAL. We found that hip fractures had longer HAL and wider NSA than vertebral fractures, whereas no statistically significant differences were found between trochanteric fractures and vertebral fractures concerning PFG. Conclusions: These data indicate that differences in PFG parameters might have a role in predisposing to femoral neck fracture.